Transmission towers spotting in power systems considering engineering and environmental aspects: A dynamic programming approach - Medeiros, Giulia O. S.; Queiroz, Anderson Rodrigo; Lima, Rodolfo M.; Pereira, Camilo R. S.; Santos, Afonso H. M.; Junior, Luiz Czank; Santos, Renato A.; Junior, Eden L. C. (International transactions on electrical energy systems, 2021)
Summary In recent years, electricity transmission systems' planning has become a subject of significant discussions worldwide due to increasing investments in renewable power and the need to optimize resources. Planning results directly affect the price of electricity for the final consumers; therefore, it is necessary to determine precise, robust, and relevant plans for the system expansion. Optimization techniques have been successfully employed in several problems associated with transmission line expansion planning, with emphasis on electricity interconnections, routing studies, and tower spotting, among others. The use of these techniques is intended to support planning processes with information that will assist the analyst in the pursuit of defined goals. The present work proposes a methodology based on dynamic programming that seeks to obtain the optimal spotting of transmission towers considering environmental (type of land use, slope, and geotechnical class of the terrain) and engineering characteristics (minimum distance between the electric conductor and ground and tensions supported of each tower type) associated with the problem. The methodology is tested in two different case studies including a real transmission line project with 39 km of extension. The results obtained show, approximately, 3.8% of cost savings obtained using the proposed approach when comparing with the real transmission line project. We also note that it is possible to verify a great similarity between the tower arrangements defined in the real project and the optimal decisions generated by the proposed approach, demonstrating its usefulness as a tool to support decision‐making in early stages of investment planning and long‐term auctions. The present work proposes a methodology based on dynamic programming that seeks to obtain the optimal spotting of transmission towers considering environmental and engineering characteristics associated to the problem when designing the optimization model. The methodology is tested for a real transmission line project and the results show its usefulness as a tool to support decision‐making.